Estabilidade de pós quasicristalinos de uma liga de Al62.2Cu25.5Fe12.3 obtidos por moagem de alta energia - Cavalcante, Danielle Guedes de Lima (2007)
Quasicrystalline structured materials bear singular properties such as elevated hardness, low superficial energy, low friction coefficient, good oxidation and corrosion resistance, high degrading resistance as well as low electrical and thermal conductivities. These materials can be obtained via conventional foundry, high energy grinding or mechanical alloying as well as fine film techniques. Nonetheless, these materials are very fragile. This makes bulk rods as used for mechanical components making also difficult. Therefore, most applications use the powder form as reinforcement in composite material and plasma spray superficial layers. One of the techniques that show excellent results is the high energy grinding technique of such quasicrystalline alloys after being obtained via the other more conventional techniques. The former technique is also known as Mechanical Milling, which allows the production of extremely fine powders (grain size below 1μm). The refined powders are often exposed to high temperatures either used for the productions of the reinforced composite materials or superficial layers. Hence, it is important to understand the thermal stability of quasicrystalline material as a function of the average particle size, temperature and atmosphere, extremely important parameters from the technological view point. The aim of this work is, therefore, to investigate the thermal stability of icosahedra quasycristalline powders of Al62.2Cu25.5Fe12.3 based alloys, which were obtained via the Mechanical Milling technique under controlled atmosphere as a function of the average particle size of the powder. Results show that the stability of the quasicrystalline powders is lost for very fine powders (after subjected to 20 hours of milling, ambient temperature). In this case, quasicrystalline phases turned into the β phase. Also, powders subjected to 10 hours of milling, the stability was lost when temperature reached 973K. On the other hand, powders subjected to 0,5 hours of milling maintained their stability up to the temperature of 973K. It has been proposed that such thermal stability is attributed to the formation of a fine aluminum oxide layer, which promotes localized chemical composition alteration and the formation of the cubic crystalline b phase as consequence. In order to avoid such oxide layer formation, the addition of bismuth was investigated. This addition was chosen in order to assess the formation of a protective external layer during the refinement process of the high energy grinding, acting as an oxygen barrier. Results show that powders ground with the addition of bismuth remained stable for longer periods of grinding. This suggests that bismuth addition does promote a formation of a fine protective layer, reducing the aluminum oxide formation. Also, the loss of the quasicrystalline structure is directly related to the formation of such aluminum oxide layer.